Higher-Order Capacities: Innovative Approaches and Methods of Research - G V Ozhiganova (Peoples' Friendship University of Russia (RUDN University), 2013)
The necessity of specific approaches and methods for the study of the higher-order spiritual, reflective and creative capacities is emphasized; their definition is given; the possibilities of their research are reviewed, including the innovative approaches and methods that go beyond the traditional psychometric paradigm.